Role of Krishi Bhavans in Agricultural Development in Thiruvananthapuram District - Suresh Nelson (Department of Agricultural Extension, College of Agriculture, 1992)
The study, ‘Role of Krishi Bhavans in Agricultural Development in Thiruvananthapuram District’ was conducted among Agricultural Extension Personnel and farmers in the three agricultural sub-divisions of the district viz. Neyyattinkara, Nedumangad and Attingal with the following specific objectives: To analyse the role of krshi Bhavans in Agricultural Development as perceived by farmers and Agricultural Extension Personnel. To study the awareness of farmers and Agricultural Extension Personnal about the concept and functioning of Krishi Bhavans. To study the attitude of farmers and Agricultural Extension Personnel towards Krishi Bhavans. To identify the constraints, if any, perceived by farmers and Agricultural Extension Personnel in the functioning of Krishi Bhavans. The study was conducted among 30 AOs. 30 AAS, 30 Karshika Vikasana Samithy Members and 60 other farmers, randomly selected from 30 krishi Bhavans of the district. The roles of Krishi Bhavans were analysed in terms of perceived importance and performance of the roles by the Agricultural Extension Personnel and farmers. Awareness was measured using the schedule developed for the study. Attitude towards Krishi Bhavans was measured using the attitude scale developed for the purpose. The characteristics of respondents were quantified using either adopted scales or schedules developed for the study. Constraints in the functioning of Krishi Bhavans were also identified as perceived by Agricultural Extension Personnel and farmers. Out of the thirty five identified roles, seven roles were perceived as important by all the four categories of respondents viz. AOs, AAS, Karshika Vikasana Samithy Members and other farmers. Of the seven roles, five were perceived by all of them as being adequately performed. The roles which were not adequately performed according to them were (i) Conducting method demonstrations, result demonstrations and Minikit trials in farmers’ fields. (ii) Arranging loans from Banks and Societies to farmers for agricultural purposes. Majority of the respondents ie. 56.67 per cent of AOs, 53.33 per cent of AAs, 56.67 per cent of Karshika Vikasana Samithy Members and 53.33 per cent of other farmers were having higher level of awareness about Krishi Bhavans. Job commitment of AOs was positively and significantly related to their awareness. None of the selected characteristics of AAs had significant relationship with their awareness. Education, social participation, contact with extension agency, innovativeness and scientific orientation of Karshika Vikasana Samithy Members and social participation, information source utilisation and innovativeness of other farmers were positively and significantly related with their awareness about Krishi Bhavans. Less than half of AOs and AAs (46.67 per cent each) and majority of Karshika Vikasana Samithy Members (60 per cent) and other farmers (56.67 per cent) were found to have high degree of attitude towards Krishi Bhavans. Job satisfaction and job commitment of AOs and job satisfaction of AAs were found to have positive and significant relationship with their attitude towards Krishi Bhavans. Contact with extension agency, Scientific orientation and awareness about Krishi Bhavans of Karshika Vikasana Samithy Members and contact with extension agency of other farmers were found to have positive and significant relationship with their attitude towards Krishi Bhavans. Lack of clerical support in Krishi Bhavan was the most important constraint perceived by AOs while ‘Lack of facilities in Krishi Bhavans was perceived as the most important constraint by AAs. The five serious constraints identified by Karshika Vikasana Samithy Members and other farmers were high labour cost, conversion of paddy fields into coconut and banana gardens making tiller ploughing difficult lack of irrigation water in time, inadequate and untimely supply of inputs and high cost of cultivation.